2014
DOI: 10.7567/jjap.53.09pb05
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and dielectric properties of silver–barium titanate nanocomplex materials by wet chemical approach

Abstract: To develop ceramic capacitors with a high effective dielectric constant, we attempted to fabricate BaTiO 3 (BT) complexes with embedded Ag nanoparticles by wet chemical processes. Ag nanoparticle-adsorbed dendritic BT particles, Ag-BT hybrid particles, were synthesized from the solgel-derived precursor gel powders containing Ag, Ba, and Ti by hydrothermal treatment. These particles were pressed with BT fillers and TiO 2 precursor nanoparticles into green compacts, and then, the green compacts were chemically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Other research groups reported the synthesis of single-crystal BaTiO 3 [ 27 ], Ba 1− x Sr x TiO 3 [ 28 ] and SrTiO 3 dendrites [ 29 ]. We have also reported dendritic Ag-BaTiO 3 hybrid particles by using the gels derived by the sol-gel process [ 15 ]. Such dendritic growth is promoted under the non-equilibrium condition, in which the growth rate of crystals sufficiently exceeds the mass transport rate of ions for the crystal growth (diffusion-limited aggregation phenomena) [ 25 , 27 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research groups reported the synthesis of single-crystal BaTiO 3 [ 27 ], Ba 1− x Sr x TiO 3 [ 28 ] and SrTiO 3 dendrites [ 29 ]. We have also reported dendritic Ag-BaTiO 3 hybrid particles by using the gels derived by the sol-gel process [ 15 ]. Such dendritic growth is promoted under the non-equilibrium condition, in which the growth rate of crystals sufficiently exceeds the mass transport rate of ions for the crystal growth (diffusion-limited aggregation phenomena) [ 25 , 27 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the local concentration of Ag + ions around the growing SrTiO 3 dendrites increases, and these Ag + ions react with OH − ions and immediately form nanocrystalline precipitates on the surface of SrTiO 3 dendrites. Ag 2 O is expected to be formed in basic aqueous solutions at room temperature, but Ag 2 O is then reduced under the hydrothermal conditions [ 15 ]. As a result of competitive formation reactions of Ag and SrTiO 3 around the precursor gels, Ag nanoparticle-loaded SrTiO 3 hybrid nanoparticles can be obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] We have also reported metal= insulator composites such as titanium metal=barium titanate (Ti=BT) and silver=BT (Ag=BT) composite materials with effective dielectric constants of over 10 3 , which were prepared by a low-temperature process utilizing hydrothermal reactions below 200 °C. 6,7) These composites are classified as percolation materials, and their dielectric properties are significantly influenced by the distribution state of metal particles. 7,8) However, as it is difficult to homogeneously distribute metal particles in insulator layers, metal=insulator composites with a different structure should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…6,7) These composites are classified as percolation materials, and their dielectric properties are significantly influenced by the distribution state of metal particles. 7,8) However, as it is difficult to homogeneously distribute metal particles in insulator layers, metal=insulator composites with a different structure should be investigated. In this study, we focus on the microstructure of boundarylayer (BL) capacitors.…”
Section: Introductionmentioning
confidence: 99%